Intravenous Vitamin C for Cancer Therapy – Identifying the Current Gaps in Our Knowledge - Carr, Anitra C.; Cook, John (Frontiers in Physiology, 2018)
The use of intravenous vitamin C for cancer therapy has long been an area of intense controversy. Despite this, high dose intravenous vitamin C has been administered for decades by complementary health care practitioners and physicians, with little evidence base resulting in inconsistent clinical practice. In this review I pose a series of questions, of relevance to both researchers and clinicians, and also patients themselves, in order to identify current gaps in our knowledge. These questions include: Do oncology patients have compromised vitamin C status? Is intravenous the optimal route of vitamin C administration? Is intravenous vitamin C safe? Does intravenous vitamin C interfere with chemotherapy or radiotherapy? What are the relevant mechanisms of action? Does intravenous vitamin C decrease the toxic side effects of chemotherapy? What are the optimal doses, frequency and duration of intravenous vitamin C therapy? Researchers have made massive strides over the last 20 years and have addressed many of these important aspects, such as the best route for administration, safety, interactions with chemotherapy, and potential mechanisms of action. However, we still do not know the answers to a number of fundamental questions around best clinical practice, such as how much, how often and for how long to administer intravenous vitamin C to oncology patients. These questions point the way forward for both basic research and future clinical trials.